2023
DOI: 10.31557/apjcp.2023.24.5.1797
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-Specific Membrane Antigen (PSMA) Expression in The Neovasculature of High Grade Gliomas (Histopathological and Immunohistochemical Study)

Mona Abdel Maguid,
Menna-t-Allah Saad El Dine,
Samia Gabal
et al.

Abstract: Background: Prostate-specific membrane antigen (PSMA) was first noticed in prostate cancer cells, thereafter, It has been found in the endothelial cells of neovasculature in a variety of tumors, but not in normal vascular endothelium, This specificity makes PSMA an ideal molecule for vascular targeting in Cancer theranostics (i.e., combined diagnostic and therapeutic). Objectives: The objective of this study was to evaluate the immunohistochemical (IHC) expression of PSMA in the neovasculature (identified by C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Abdel Maguid et al 21 also recently (2023) found that PSMA expression in endothelial cells of HGG neovasculature are specific and significant. Additionally, increased glioma vascular PSMA staining has been associated with significantly elevated tumor metabolic activity (P < 0.001), significantly shorter median survival time (1.5 years with vs 11.3 years without, P < 0.001), and significantly higher Ki-67 index (42% with vs 8% without, P < 0.001).…”
Section: Histopathologymentioning
confidence: 91%
See 3 more Smart Citations
“…Abdel Maguid et al 21 also recently (2023) found that PSMA expression in endothelial cells of HGG neovasculature are specific and significant. Additionally, increased glioma vascular PSMA staining has been associated with significantly elevated tumor metabolic activity (P < 0.001), significantly shorter median survival time (1.5 years with vs 11.3 years without, P < 0.001), and significantly higher Ki-67 index (42% with vs 8% without, P < 0.001).…”
Section: Histopathologymentioning
confidence: 91%
“…Rat gliomas have been shown to have increased uptake of PSMA tracers in the peritumoral area and areas of strong astrocyte activation and decreased uptake in central areas 16 . Several studies have additionally confirmed high PSMA staining in glioma vasculature 17,18,21 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations